Mathematical mindsets unleashing students' potential through creative mathematics, inspiring messages and innovative teaching - Boaler, Jo 1964- (Jossey-Bass, 2022)
"Jo Boaler, a professor of mathematics at Stanford University, has followed thousands of students through middle and high schools studying their learning of mathematics and the most effective ways to help them become high achievers. In this book, she shows teachers and parents how to unleash the math potential in all students. Contents include The Brain and Mathematics Learning The Power of Mistakes and Struggle What Is Math Really? Creating Mathematical Mindsets Rich Mathematical Tasks--Curiosity, Creativity and Connections Strategies for Promoting Equity Assessing for a Growth Mindset in Math The revision will include approximately 25% updated and new material, including: An infusion of new research and ideas and resources from the last five years The integration of ideas around the teaching of data science K-12 A social justice perspective -- with examples of social justice tasks These chapters are specifically designed to equip teachers with the most up-to-date practical research to help inspire a love of math in all of their students."--